Rancang Bangun Sistem Pendukung Keputusan Pemilihan Sales Terbaik pada PT Caturadiluhur Sentosa Menggunakan Metode SAW - Ampu Syura Rizki; Yulistia Yulistia (Transformasi Manageria: Journal of Islamic Education Management, 2023)
PT Caturadiluhur Sentosa Palembang is a company engaged in the distribution, logistics, and retail of building materials. PT Caturadiluhur Sentosa Palembang has several obstacles, namely the criteria for determining the best current sales by determining the largest turnover only. So that the current best sales appraisal system is considered less effective and unfair. The system built aims to build the best sales decision support system that can manage sales data and assessment parameters properly. The system built can manage sales data, criteria data, store sales appraisal data, and calculate sales value using the SAW method. The system is built using the iteration method. The result of this research is a decision support system that gives the best sales ranking based on the results of the assessment calculated using the SAW method. Keywords: Decision Support System, Iteration, SAW